Analisis Penggunaan Modal Kerja Petani Padi Sawah di Desa Lasembangi Kecamatan Lasalimu Kabupaten Buton - Agus Rismawan; R. Marsuki Iswandi; Wa Ode Yusria (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
This study aims to find out how the sources and methods of capital for lowland rice farmers in Lasembangi Village, find out how much and efficient working money is used by lowland rice farmers in Lasembangi Village, and find out whether Lowland rice farmers can return the money used during the production of their farm in Lasembangi Village. This research was conducted from November 2021 to February 2022. The population in this study were 42 lowland rice farmers, using a saturated sampling technique. This study took the entire lowland rice farmer population as a sample, namely 42 lowland rice farmers. The data obtained were analyzed using the formula of Total Cost (TC), Net Profit Margin (NPM) and analysis of Return On Investment (ROI). The results showed that the source of capital used for lowland rice farming came from own money, as many as 19 people (45.24%), and additional loan capital from as many as 23 people (54.76%). The working capital used for lowland rice farming for farmers who borrow extra money is IDR5,290,351.03 - per hectare and gets an efficiency value of 4,303. This shows that lowland rice farming for farmers who borrow additional capital is still not efficient because the value of the efficiency is greater than 1. Farmers with their money need working capital of IDR4,778,893,275 - per hectare and get an efficiency value of -1,259. This shows that farmers with their capital farming lowland rice are relatively inefficient because the efficiency value is smaller than 1. Lowland rice farming in Lasembangi Village is declared profitable and feasible to cultivate because lowland rice farmers can return the farming capital used during the production process. The ROI obtained for farmers who use additional loan capital is 154%, which means that the farm gains 154% of the profit from the amount of money issued so that the farming capital can be covered. In comparison, the farmer who owns the capital gets an ROI of 124%, which means the farm gets 124% profit from the amount of money issued so that farming capital can be covered.